Menggunakan Aplikasi Web Sebagai Informasi Di Cv. Karya Mulia - Raka Aditya (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2023)
The development of the business world in Indonesia is marked by a situation of rapid change that is difficult to predict. This is due to the influence of the economic crisis which is still ongoing. The real sector is the sector that was most affected by the earliest and the heaviest. CV. Karya Mulia, which is located at Jl. Bandungrejo No. 65 Mranggen Demak – Indonesia is a company engaged in graphic design and printing services that wants to progress and develop because it has been established for about 10 years, which at this time is required to compete with other companies. With this situation, companies are required to market their products more quickly and efficiently